Locomotive [videorecording (DVD)] - Floca, Brian (Dreamscape Media, LLC, 2014)
It is the summer of 1869, and trains, crews, and families are traveling together, riding America's brand new transcontinental railroad. The pages come alive with the details of the trip and the sounds, speed, and strength of the mighty locomotives; the work that keeps them moving; and the thrill of travel from plains to mountain to ocean. Come hear the hiss of the steam, feel the heat of the engine, watch the landscape race by. Come ride the rails, come cross the young country!